2023
DOI: 10.21037/cdt-22-439
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging evaluation of arteriovenous fistulas and grafts: a clinical practice review

Abstract: Arteriovenous fistulas (AVFs) and grafts (AVGs) are the preferred forms of vascular access for hemodialysis in patients with severe renal dysfunction. Multimodality imaging plays an important role in the pre-procedural evaluation of these patients. Ultrasound is often used for pre-procedural vascular mapping in preparation for the creation of an AVF or AVG. Pre-procedural mapping includes a comprehensive evaluation of the arterial and venous vasculature including evaluation of vessel diameter, stenosis, course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The reason our study data were slightly higher than other studies may be because firstly, we excluded advanced-aged surgical patients, and secondly, in patients with poor vascular conditions, we tried to select larger diameters by preoperative Doppler blood vessel ultrasonography. Actually, clinicians can also use multimodality imaging to evaluate AVFs and grafts for precise assessment ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason our study data were slightly higher than other studies may be because firstly, we excluded advanced-aged surgical patients, and secondly, in patients with poor vascular conditions, we tried to select larger diameters by preoperative Doppler blood vessel ultrasonography. Actually, clinicians can also use multimodality imaging to evaluate AVFs and grafts for precise assessment ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…This diagnostic method excels at precisely delineating the anatomy of the fistula, assessing its impact on nearby structures, and aiding in the development of an appropriate treatment plan. The non-contrast CT is only capable of revealing a perirenal hematoma [28]. Still the color Doppler ultrasound is well suited to detect a renal AV fistula [29]; phenomena such as a region of high-velocity shift and a low-resistive index can be indicative of AV fistulas [30].…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, AVF maturation can also be influenced by vein depth, hemodynamic limitations, blood inflow problems, such as native arterial disease, arteriovenous anastomosis, or outflow problems, such as proximal venous stenosis or collateral veins. 4 Also, cardiovascular comorbidities and a thicker media layer of the radial artery emerged as predictive factors for primary radiocephalic fistila patency, providing valuable insights into the multifaceted determinants of long-term success in radiocephalic fistila procedures. 5 Moreover, diabetes can also cause AVF obstruction due to hypercoagulation, hyperlipemia, hypoalbuminemia, or high insulin levels associated with hyperlipemia.…”
Section: Introductionmentioning
confidence: 99%
“…According to the KDOQI (Kidney Disease Outcomes Quality Initiative) guidelines, patients requiring hemodialysis should create primary distal forearm AVFs with a snuffbox fistula or distal radiocephalic fistula, as it preserves the vascular integrity of the proximal forearm and arm for subsequent AVF creation. 1 Although AVFs have a high initial failure rate, it is estimated that between 30% and 70% of radiocephalic AVFs fail. 2 It has been suggested that age, female gender, diabetes, and small diameters of the radial artery and vein are the most significant factors influencing early failure of radiocephalic fistulas.…”
Section: Introductionmentioning
confidence: 99%